Changes of environmental and recreational conditions in perm region against the background of global warming - Shklyaev, V.A.; Ermakova, L.N.; Isakov, S.V.; Kulakova, S.A.; Shklyaeva, L.S. (Perm Federal Research Centre Journal, 2017)
Changes of various characteristics of inversion in Perm from 1959 to 2012 are considered. It was found that the greatest frequency of surface and elevated temperature inversions was observed from 1959 to 1968. In the subsequent period there was a significant decrease in the frequency of inversions, which in recent years has started to increase again. The results of the observations by the temperature profiler indicate the presence of a "heat island".The use of a digital elevation model with the help of ArcGIS made it possible to estimate the local features of the territory in the incoming short-wave radiation. Layers of exposure and slope were created, which then were divided into three parts with the help of ArcGIS: the base of the hill, the slope and the top. On the basis of this, zones of change in wind speed were distinguished.The time variability of equivalent-effective temperatures (EET) over the 15-year period is considered. The main trends in the changes of EET in warm and cold periods of the year are revealed. It is established that in the cold period of the year, on the territories of the studied objects there observed a decrease in the values of EET by the end of the period under study, which is the most noticeable in February and March. The paper presents zoning of the territory of Perm region by the complex indicator of comfortable weather conditions.